UN SECRETARY-GENERAL NORMATIVE CAPABILITY TO INFLUENCE THE SECURITY COUNCIL DECISION-MAKING PROCESS - D. G. Novik; V. A. Plotnikov (Vestnik MGIMO-Universiteta)
The present article studies the issue of the interrelation between the senior UN official - the Secretary-General and the main UN body - the Security Council. The nature of the Secretary-General role is ambiguous since the very creation of the UN. On one hand, the Secretary-General leads the Secretariat - the body that carries out technical and subsidiary functions in relation to other UN Main Bodies. This is the way the Secretary-General position was initially viewed by the UN authors. On the other hand, the UN Charter contains certain provisions that, with a certain representation, give the Secretary-General vigorous powers, including political ones. Since the very beginning of the UN operation the Secretary-Generals have tried to define the nature of these auxiliary powers, formalize the practice of their use. Special place among these powers have the provisions given in the Charter article 99. This article give to the Secretary-General the right to directly appeal to the Security Council and draw its attention to the situation that, in his (Secretary-General's) opinion may threaten the international peace and security. This right was used by some Secretary-Generals during different crises occurred after the creation of the UN. This article covers consecutively the crisis in Congo, Iran hostage crisis and the situation in Lebanon. These are three situations that forced Secretary-Generals Hammarskjold, Waldheim and de Cuellar to explicitly use their right to appeal to the Security Council. Other cases in UN history involving the Secretary-General appealing to the Security Council while mentioning article 99 cannot be considered as the use of the nature of this article in full sense of its spirit. Such cases were preceded by other appeals to the Council on the same situations by other subjects (notably, the UN member states) or other actions that made Secretary-General to merely perform its technical function. The main research problem here is the search for the UN instrument that could grant the Secretary-General with political powers I addition to existing administrative ones. The outcomes of the analysis show that the main instrument of such kind is the UN Charter Article 99. However, the degree of its usage activity is decreasing over time.